PENGARUH DEBT TO ASSET , RETURN ON ASSET , UKURAN KOMITE AUDIT, UKURAN KAP DAN UKURAN PERUSAHAAN TERHADAP WAKTU PELAPORAN AUDIT PERTAMBANGAN 2019 - 2021 - Laurenza Jenita Tjahyadi; Juan Carlos Pangestu (Politeknik Ganesha Medan, 2023)
This study aims to examine the effect of Debt To Assets, Return On Assets, Audit Committee Size, KAP Size, and Company Size on Audit Reporting Time. The type of research used in this research is quantitative research. Determination of the sample used in this study using a purposive sampling method based on certain criteria. The samples taken as the object of this study totaled 19 mining companies listed on the Indonesia Stock Exchange (IDX) with an observation period of three (3) years, namely 2019-2021. The data analysis method used in this study uses a multiple linear regression analysis model using the SPSS 24 application. The results of this study indicate that the variables Return On Assets, Audit Committee Size, KAP Size have a significant effect on Audit Reporting Time. Meanwhile, the Debt To Asset and Company Size variables have no significant effect on Audit Reporting Time. Based on the research that has been done, the advice that can be given to future researchers is to expand the factors that influence reporting time such as using Cashflow or changing the type of research to qualitative by interviewing auditors or company management.